Português Português (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2022)
The present article is about the civil liability of the Legislative State, specifically, in the case of the normative acts are typified in the Law of Administrative Improbity.At first, it seeks to understand the conceptualization of the state's civil liability figure and the juridical nature, and then including analyzing the theories adopted in Brazilian reality.In the second moment, it is presented what is the function of the Legislative exercise, and the possible civil liability for acts performed that harm the individual. In the third and last moment, the discussion presents the definition of Administrative Improbity and the evolution of it, especially in legislative acts, and their application within of that Law and the specific case.In the end, it is concluded that the personal responsibility of the legislator is liable if applicable willful misconduct in the face of the demonstrative conditions of abuse or deviation from the reign, even if in a narrow way in order not to impinge on the constitutional protection to which parliamentary action is safeguarded.